2022
DOI: 10.3390/ph16010003
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal Uses, Phytochemistry, and Therapeutic Potentials of Litsea glutinosa (Lour.) C. B. Robinson: A Literature-Based Review

Abstract: Litsea glutinosa (Lour.) C. B. Robinson, belonging to the family Lauraceae, is a multipurpose and fast-growing evergreen or deciduous tree that has been traditionally used for numerous purposes such as treatment for diarrhea, dysentery, abdominal pain, indigestion, gastroenteritis, edema, traumatic injuries, colds, arthritis, asthma, diabetes, pain relief, and poignant sexual power. This study aimed to summarize the chemical reports, folk values, and phytopharmacological activities of L. glutinosa, based on av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Tree, trunk bark blackish grey, leaves elliptic to oblongelliptic, young leaves pilose; flowers unisexual, yellowish in colour, fruits berries small 5-6mm across. Besides properties to cure of other diseases, it is useful in lifestyle diseases like asthma, diabetes, pain relief, and poignant sexual power [20] . Melochia corchorifolia L. (Malvaceae) Tikiokra, Bilipatr, Bon-pat, Chocolate Weed.…”
Section: Resultsmentioning
confidence: 99%
“…Tree, trunk bark blackish grey, leaves elliptic to oblongelliptic, young leaves pilose; flowers unisexual, yellowish in colour, fruits berries small 5-6mm across. Besides properties to cure of other diseases, it is useful in lifestyle diseases like asthma, diabetes, pain relief, and poignant sexual power [20] . Melochia corchorifolia L. (Malvaceae) Tikiokra, Bilipatr, Bon-pat, Chocolate Weed.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes from all antioxidant tests in this study demonstrated that the leaf water extract of L. martabanica displayed considerable antioxidant properties in both DPPH and superoxide radical assays. Moreover, previous research and literature reviews have highlighted the antioxidant activity present in plants of the genus Litsea, with this attribute being observed across different parts of the plants, including leaves, roots, and stems [52][53][54]. For example, the methanolic extract of L. glutinosa has demonstrated antioxidant properties including hydrogen peroxide scavenging activity, total antioxidant capacity, nitric oxide scavenging activity assay, and reducing power test [55].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia in diabetics results in micro- and macrovascular consequences, including cardiovascular disorders, diabetic retinopathy, neuropathy, and nephropathy [ 3 , 5 ]. L. glutinosa is a traditional herbal remedy that is frequently used to treat diarrhea and dysentery [ 55 ]. It is demonstrated though the current research that the methanolic leaf extract from the L. glutonosa plant species had a considerable impact in reducing diabetes in mice that had been induced with STZ.…”
Section: Discussionmentioning
confidence: 99%